1997
DOI: 10.1080/07391102.1997.10508150
|View full text |Cite
|
Sign up to set email alerts
|

Internal DNA Modes Below 25 cm−1: A Resonance Raman Spectroscopy Observation

Abstract: The first resonance Raman scattering observation of the low-frequency (LF) region (below 40 up to 12 cm-1) of DNA motions is presented. Since the concentration of the studied DNA solution was very low (1 mg/ml), the spectra features reflect internal vibrations of the macromolecule. The decomposition of the spectra into Lorentzians clearly indicate three intrahelical DNA modes: the corresponding peaks are located at the frequencies 16, 19, and 23 (+/- 1) cm-1. This result is in agreement with our quasi-continui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…While no experimental data on IR absorption is available in this frequency range, Raman scattering [23] clearly indicates resonance peaks around 20 cm )1 (16.2, 19.3 and 23.3 cm )1 ).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…While no experimental data on IR absorption is available in this frequency range, Raman scattering [23] clearly indicates resonance peaks around 20 cm )1 (16.2, 19.3 and 23.3 cm )1 ).…”
Section: Resultsmentioning
confidence: 94%
“…Unlike most of the other studies on DNA theoretical spectroscopy [11,23,24,25,26], we did not oversimplify the DNA structure and considered all possible interatomic interactions. To do that, we employed the methods of molecular mechanics and normal mode analysis, which enable rigorous calculations of biopolymer structure and dynamics (reviewed in Ref.…”
Section: Discussionmentioning
confidence: 96%
“…Hence, the Raman effect arising from nonlinear mixing interactions between the EM field and the naturally occurring phonon modes is a second-order optical process and can give unique information regarding to transitions into exited states not available from first-order photon absorption. DNA in various forms (i.e., thin films, fibers 18 , and solutions 19 ) has been studied to determine the Raman signature dependence on humidity 18 , helix conformation 11,20 , molecular packing (intrahelical and interhelical modes) [21][22][23][24] , and light polarization 23 . Active Raman absorption modes as low as 25 cm -1 , 60 cm -1 and 90-100 cm -1 have been reported 17,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been found for a variety of proteins, thus suggesting the possibility that specific vibrations can be identified using optical spectroscopy. A number of proteins have been measured spectroscopically with Raman and traditional Fourier transform infrared (FTIR) transmission techniques (Lindsay et al 1988;Lisy et al 1997;Powell et al 1987Powell et al , 1991. While extensive Raman spectroscopy studies have been performed, there is some disagreement among various research groups on band identification, possibly due to the application of complex Lorentzian line-fitting procedures for extracting weak contributions to the main elastic scattering peak (Lisy et al 1997;Weidlich et al 1990).…”
Section: Terahertz Measurementsmentioning
confidence: 99%
“…A number of proteins have been measured spectroscopically with Raman and traditional Fourier transform infrared (FTIR) transmission techniques (Lindsay et al 1988;Lisy et al 1997;Powell et al 1987Powell et al , 1991. While extensive Raman spectroscopy studies have been performed, there is some disagreement among various research groups on band identification, possibly due to the application of complex Lorentzian line-fitting procedures for extracting weak contributions to the main elastic scattering peak (Lisy et al 1997;Weidlich et al 1990). Coherent vibrations of bound chromophores have been identified (Parak 2003;Zhu et al 1996), but to date no collective vibrations have been identified.…”
Section: Terahertz Measurementsmentioning
confidence: 99%